Entrenching heterosexuality through language in South African Life Orientation (LO) textbooks - M. Wilmot; D. Naidoo (Perspectives in Education, 2018)
Studies of the representation of sexualities in textbooks have tended to focus on inclusion and coverage of diverse content through thematic analysis. This analysis of a sample of LO textbooks is framed by the systematic linguistic framework of critical discourse analysis (CDA), specifically Fairclough’s (2001) theory of discourse as ideological meanings encoded in text. The sections on sex education in three popularly used LO textbooks have been analysed to make explicit the heteronormative meanings conveyed through language used. This article provides insight into how the language in the LO texts function to legitimate the dominant discourse of a particular type of heterosexuality: monogamy for the primary purpose of reproduction. The implications of this bias are raised and recommendations for fair representation of LGBT sexual orientations are made.